2015
DOI: 10.1021/acs.energyfuels.5b01629
|View full text |Cite
|
Sign up to set email alerts
|

Branched Ketone Biofuels as Blending Agents for Jet-A1 Aviation Kerosene

Abstract: In this investigation a range of ketone biofuels produced from the alkylation of isoamyl alcohol and isobutanol were examined as potential blending agents with Jet A-1 aviation kerosene. The fuels were synthesised under solvent-free conditions using a Pd/C catalyst with K3PO4, previously reported for the alkylation of acetone, butanol, ethanol (ABE) fermentation mixtures. Reasonable yields and selectivity were achieved for branched alkylation products with up to 61 % produced from isoamyl alcohol and 64 % from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was reported that branched ketones can have a positive effect on fuel properties. In a study by Donnelly, et al., the production and fuel analysis of C 8 –C 15 branched ketones through the alkylation of branched alcohols (isoamyl alcohol or isobutanol) and acetone with Pd/C and K 3 PO 4 was carried out . When in a 20 % blend with Jet A‐1, all fuel molecules produced suppressed the melting point below that of pure Jet A‐1, all were found to be below the maximum viscosity of 8 mm 2 s −1 , and all were above the minimum Jet A‐1 energy density of 42.8 MJ kg −1 .…”
Section: Oxygen Effectsmentioning
confidence: 99%
“…It was reported that branched ketones can have a positive effect on fuel properties. In a study by Donnelly, et al., the production and fuel analysis of C 8 –C 15 branched ketones through the alkylation of branched alcohols (isoamyl alcohol or isobutanol) and acetone with Pd/C and K 3 PO 4 was carried out . When in a 20 % blend with Jet A‐1, all fuel molecules produced suppressed the melting point below that of pure Jet A‐1, all were found to be below the maximum viscosity of 8 mm 2 s −1 , and all were above the minimum Jet A‐1 energy density of 42.8 MJ kg −1 .…”
Section: Oxygen Effectsmentioning
confidence: 99%
“…A model compound approach is utilized to represent complex real-world mixtures of bio-oil constituents in terms of their most prominent molecular components and is consistent with methods of prior studies. As per the experimental yield data (Table S1), seven groupings of torrefaction bio-oil product compounds are considered here as model compounds: carboxylic acids as acetic acid, light oxygenates as acetol, furanics as furan and furfural, aromatics as toluene, multifunctional phenolics as guaiacol, alkylated phenolics as m -cresol, and anhydrous sugars as levoglucosan. These model compounds are then converted to C6+ transportation fuels and specialty chemicals via a host of upgrading chemistries, including ketonization, alkylation, hydrolysis and oxidation, hydrogenation, and hydrodeoxygenation (HDO) .…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that blends of biofuels and conventional jet fuels can reduce emissions of greenhouse gases and particulate matter, contributing to cleaner combustion and reduced environmental impact. However, the stability, cold flow properties, and combustion characteristics of these blends are critical parameters that need continuous monitoring and optimization to meet the operational requirements of commercial aviation [71,72].…”
Section: Blending With Conventional Jet Fuelsmentioning
confidence: 99%